Micro-Raman, FTIR, SEM-EDX And Structural Analysis Of The Canakkale Meteorite - Ünsalan, Ozan; Yılmaz, Ayberk; Bölükbaşı, Olcay; Öztürk, Burak; Esenoğlu, Hasan Hüseyin; Örnek, Cihan Yavuz; ILDIZ, GÜLCE ÖĞRÜÇ (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2012)
This study demonstrates for the first time, the spectroscopic characterization of Canakkale Meteorite that fell at Canakkale, Republic of Turkey (40 degrees 8'44 '' N; 26 degrees 24'23 '' E). The olivine group [(Mg, Fe)(2)SiO4], enstatite [Mg2Si2O6] (one of the orthopyroxene minerals) and plagioclase were identified by the micro-Raman and FTIR spectroscopies and EDX-SEM analyses. This meteorite has not yet been classified in the World's Database of Meteorites. The aim of this study is to investigate this meteorite by vibrational spectroscopic techniques and open the possibility to classify it and list in the World's Database of Meteorites. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: micro-raman spectra; FTIR spectroscopy; Canakkale meteorite; olivine; pyroxene; enstatite; vibrational-spectra; spectroscopy; mineralogy; chondrite; pyroxenes; tool; Mikro-Raman spektrumu; FTIR spektroskopisi; Çanakkale göktaşı; olivin; piroksen; enstatit; titreşim-spektrumları; spektroskopisi; mineraloji; kondrit; Makedonya; piroksenler; araç; Macedonia